An Assessment of the Relationship Among Cargo-Throughput, Vessel Turnaround Time and Port-Revenue in Nigeria. (A Study of Lagos Port Complex) - Buhari, Sodiq Olusegun; Ndikom, Obed; Theophilus, Nwokdi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
A knowledge based economy remains the propeller for development in most developing nations. Adequate knowledge of the quantitative relationship among vessel turnaround-time, Cargo-throughput and revenue generated by a seaport constitute a determinant factor in forecasting the long-run financial performance of terminal operators and ports authorities. The study investigated the quantitative relationship among vessel turnaround-time, cargothroughput and port-revenue and the effect of such relationship on port performance in Nigeria. Since port performance, measureable by the level of revenue generated over time is dependent on cargo-throughput and ship turnaround-time, multiple regression method was used in analyzing the time series data of 15 years. The result of the analysis reveals a significant impact of ship turnaround-time and cargo-throughput on port-revenue. The relationship between port-revenue and each of cargo-throughput and ship turnaround-time is: Y = 106.22X1 + 55.064X2 -10753.216 + e. The study recommended improved investment in port infrastructure to improve ship turnaround-time and cargo-throughput, and maximize port-revenue.